Do Fiscal Spillovers Matter? - Weber, Sebastian (International Monetary Fund, 2011)
The paper assesses the impact of fiscal spillovers on growth in the context of a coordinated exit from crisis management policies. We find that despite potentially sizeable domestic effects from consolidation, aggregate negative spillovers to other countries are likely to be contained in 2011-2012 unless fiscal multipliers and/or imports elasticities are very large. Small and open European economies, however, will be substantially affected in any case. In contrast, the coordinated exit from fiscal stimulus will have limited direct effect on European peripheral countries since they are relatively closed, with the notable exception of Ireland